Cash-Flow News and the Investment Effect in the Cross Section of Stock Returns - Mao, Mike Qinghao; Wei, K. C. John (Management Science, 2016)
This study provides novel evidence that cash-flow news quantitatively explains the investment effect in the cross section of stock returns. The negative return predictability of asset growth, investment growth, and accruals is evident only through the cash-flow news component of returns. The cash-flow news returns associated with investment-sorted portfolios exhibit a reversal from the preformation period to the postformation period. Such a return reversal is in line with reversals in firm fundamentals and becomes stronger for stocks with higher information uncertainty. Our findings are consistent with the expectational errors hypothesis and fail to support the risk-based explanation for the investment effect. This paper was accepted by Neng Wang, finance.